2003
DOI: 10.1002/mrm.10398
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of magnetization transfer during on‐resonance water saturation. A new approach to detect mobile proteins, peptides, and lipids

Abstract: The mechanism of magnetization transfer (MT) between water and components of the proton spectrum was studied ex vivo in a perfused cell system and in vivo in the rat brain (n ‫؍‬ 5). Water was selectively labeled and spectral buildup consequential to transfer of longitudinal magnetization was followed as a function of time. At short mixing time (T m ), nitrogen-bound solventexchangeable protons were observed, predominantly assigned to amide groups of proteins and peptides. At longer T m , intramolecular nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
267
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(288 citation statements)
references
References 40 publications
20
267
1
Order By: Relevance
“…This was supported by an NMR study reporting that the amide protons of mobile protein/peptide side chains (Gln, Asn) and backbone amides resonate at 6.8 ppm and 8.2-8.4 ppm (2.1 ppm and 3.5-3.7 ppm downfield of water resonance) range, respectively (28). Zhou et al demonstrated in two models of orthotopic murine glioma that APT imaging could clearly differentiate viable glioma (hyperintense) from radiation necrosis (hypointense to isointense), and that the APT signal of the tumor decreased substantially after radiation (19).…”
Section: Discussionmentioning
confidence: 77%
“…This was supported by an NMR study reporting that the amide protons of mobile protein/peptide side chains (Gln, Asn) and backbone amides resonate at 6.8 ppm and 8.2-8.4 ppm (2.1 ppm and 3.5-3.7 ppm downfield of water resonance) range, respectively (28). Zhou et al demonstrated in two models of orthotopic murine glioma that APT imaging could clearly differentiate viable glioma (hyperintense) from radiation necrosis (hypointense to isointense), and that the APT signal of the tumor decreased substantially after radiation (19).…”
Section: Discussionmentioning
confidence: 77%
“…Selective irradiation is possible because there is a composite amide proton resonance at approximately 3.5 ppm downfield from the water resonance (21)(22)(23), and in the brain, amide protons exchange with water protons at a rate (k) of about 30 times per second (14). Thus, the frequency difference (⌬) with the water resonance is generally sufficient to provide conditions of slow exchange on the NMR time scale (⌬Ͼ Ͼk).…”
Section: Theorymentioning
confidence: 99%
“…To ensure that a subject is being imaged in the same physiologic state, and to correlate changes over time in the PET and MRI signals in response to an intervention, thus often requires that the data be acquired simultaneously. To give just one example, one might want to monitor dynamic changes in tumor physiology with MRI [e.g., cellularity by diffusion measurements (24), macromolecular environment (25,26), vasculature by contrast enhancement (27)] while imaging the delivery of a radiolabeled therapeutic agent to, or assessing the biochemistry of, the tumor. Simultaneous acquisition of PET and MRI data by using an integrated imaging device is, therefore, necessary to answer many important biomedical questions in dynamic, living systems.…”
mentioning
confidence: 99%